A new scoring system to predict survival in elderly advanced stage Hodgkin lymphoma patients - TOPTAŞ, TAYFUR (My University, 2024)
Predictive prognostic scoring (PS) systems are not primarily applicable to elderly patients with classical Hodgkin lymphoma (cHL). The objective of this study was to develop a PS system for these patients. The derivation cohort (DC) was utilized for model development, consisting of 97 variables. The resulting algorithm was named as Hodgkin’s Lymphoma Early Death in the Elderly within 12 months (HEDEL12). Internal and external validation cohorts (IVC and EVC) were employed for validation. A total of 286 patients were evaluated retrospectively. In DC 38 of 178 patients died within the first 12 months and overall survival (OS) at 12-month was 78.6%. Independent predictors of HEDEL12 were female sex, low albumin levels (<3.5 g/dL), and ECOG scores 2-4. According to HEDEL12 scores 0–1, OS at 12- months were 89.8% and 91.0% for IVC and EVC, respectively. The HEDEL12 scoring is useful in predicting the survival of advanced-stage cHL patients. Keywords: Elderly hodgkin lymphoma; prognostic scoring; advanced stage
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Onkoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Oncology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (Med); Yaşam Bilimleri (Life); Klinik Tıp; Moleküler Biyoloji Ve Genetik; Biyokimya Ve Moleküler Biyoloji; Clinical Medicine (Med); Life Sciences (Life); Clinical Medicine; Molecular Biology & Genetics; Biochemistry & Molecular Biology; Kanser Araştırmaları; Cancer Research; advanced stage; Elderly hodgkin lymphoma; prognostic scoring; Elderly hodgkin lymphoma; prognostic scoring; advanced stage